Digital Dopamine and Modern Learning: Educational Technology Perspectives on Digital Content Addiction - Mokhamad Yaurizqika Hadi (PT. Anagata Sembagi Education, 2026)
The proliferation of algorithmically curated digital content has introduced a neurological phenomenon increasingly referred to as